Pengaruh Waktu Pemeraman Terhadap Uji Kuat Tekan Paving Block Menggunakan Campuran Tanah, Semen dan Abu Sekam Padi dengan Alat Pemadat Modifikasi - sari, ikko rasita; adha, idharmahadi; Setyanto, Setyanto (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2016)
AbstractPaving blocks made from a mixture of portland cement or a kind of adhesive hydrolysis, water, and aggregates with or without other ingredients. In this study the process of manufacture of paving blocks will use a mix of soil, portland cement and ashes a rice husk. Moreover, curing of the paving blocks that are expected to increase the strength of paving blocks is according to SNI 03-0691-1996.Soil samples tested were from Kota Baru, South Lampung. The composition of the paving block in this study is 80% soil+15% portland cement+5% ashes a rice husk with a variety of curing time 0 day, 7 days, 14 days, 21 days and 28 days as well as to the treatment of pre-combustion and post-combustion of the sample of paving blocks. Based on the results of physical testing the original soil, USCS classify soil samples as fine-grained soil and belong to the group ML. Results from this study is the manufacture of paving blocks using silt soil, portland cement and ashes a rice husk soil material that does not meet the specifications of SNI 03-0691-1996. Ashes a rice husk does not give effect for the compressive strength of paving block and the curing time too. The longer of curing time, the compressive strength will decrease too. The highest result for the compressive strength of paving blocks post-combustion are best shown in curing time of 0 day 11,70 Mpa.Keywords: Paving blocks, silt soil, ashes a rice husk, compressive strength, curing time.